IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DAN PROFIL PELAJAR RAHMATAN LIL’ALAMIN (P5PPPRA) KEARIFAN LOKAL (STUDI KASUS MADRASAH ALIYAH DARUL ULUM KOTABARU) - Anshari, Muhammad Hafiz; Taufikkurachman; Muhamad Fadillah (Kurikula : Jurnal Pendidikan, 2024)
This research aims to describe the implementation of P5PPPRA local wisdom at Madrasah Aliyah Kotabaru and several processes carried out by the madrasah in implementing P5PPPRA activities. The study also aims to identify supporting and inhibiting factors in the implementation of P5PPPRA Local Wisdom at Madrasah Aliyah Darul Ulum Kotabaru. The research in this article uses a qualitative descriptive research method based on a case study. The location of the study is Madrasah Aliyah Darul Ulum in the Pulau Laut Utara District, Kotabaru Regency. Data sources in this research are obtained through informants, activities, and documents related to the performance of Madihin in the implementation of P5PPPRA. Data collection techniques used include interviews, observations, and documentation. Interviews were conducted with the head of the madrasah and two teachers who are part of the P5PPPRA facilitator team with the theme of Local Wisdom at Madrasah Aliyah Darul Ulum Kotabaru. Observations were made by directly observing the design, management, assessment and reporting of results, as well as evaluation and follow-up in the implementation of P5PPPRA activities at Madrasah Aliyah Darul Ulum Kotabaru.The research findings are as follows: (1) The Implementation of the Strengthening Project of Pancasila Student Profile and Rahmatan Lil'alamin Student Profile at MA Darul Ulum Kotabaru, which is in Phase E of the Merdeka Curriculum implementation, is carried out in the form of extracurricular activities by 28 students from class 10, addressing the theme of Local Wisdom with the sub-theme or topic "Madihin as an Islamic Preaching Medium in Kotabaru Regency." The allocated time for the local wisdom theme at MA Darul Ulum Kotabaru is 54 hours or 18 meetings scheduled every Thursday from October 19 to November 23, 2023. (2) During the implementation of P5PPPRA Local Wisdom activities at MA Darul Ulum Kotabaru, the head of the madrasah, as the activity coordinator along with 9 teachers in the madrasah who are part of the P5PPPRA Local Wisdom facilitator team, took several steps including the planning stage, design stage, assessment and implementation stage, and reporting and evaluation stage. (3) Supporting factors for the implementation of P5PPPRA Local Wisdom at MA Darul Ulum Kotabaru include ease of obtaining information related to Madihin and the availability of Madihin equipment. The inhibiting factors include the readiness of students in Madihin game rules and the lack of time allocation in the learning process or preparation for P5PPPRA.